Magnetic Resonance Imaging Guided Vacuum Assisted Breast Biopsy: A Phantom and Patient Evaluation of Targeting Accuracy - El Khouli, Riham H. (2009)
PURPOSE: To determine the spatial localization errors of magnetic resonance imaging (MRI) guided core biopsy for breast lesions using the hand-held vacuum assisted core biopsy device in phantoms and patients. MATERIALS AND METHODS: Biopsies were done using a 10-gauge hand-held vacuum-assisted core biopsy system (Vacora, Bard, Arizona) on a 1.5 T MRI scanner (Philips Achieva, Best, The Netherlands). A standardized biopsy localization protocol was followed by trained operators for multi-planar planning of the biopsy on a separate workstation. Biopsy localization errors were determined as the distance from needle tip to center of the target in 3 dimensions. RESULTS: Twenty MRI-guided biopsies of phantoms were performed by 3 different operators. The biopsy target mean size was 6.8 ± 0.6 mm. The overall mean three dimensional (3D) biopsy targeting error was 4.4 ± 2.9 mm. Thirty two MRI breast biopsies performed in 22 patients were reviewed. The lesion mean size was 10.5 ± 9.4 mm. The overall mean 3D localization error was 5.7 ± 3.0 mm. No significant differences between phantom and patients biopsy errors were found (p-value >0.5). CONCLUSION: MRI guided hand-held vacuum assisted core biopsy device shows good targeting accuracy and should allow localization of lesions to within approximately 5–6 mm.